Breadth and Depth. - MATSUDAIRA, KATE (Communications of the ACM, 2017)
The author presents career advice for computer software developers and engineers, particularly focusing on the need for developers to continue learning in order to avoid becoming obsolete. She discusses the need for developers and engineers to acquire deep knowledge and to specialize in a particular area of expertise.